Purification and Characterization of Transglutaminase from Local Streptomyces Sp. TTA 02 SDS 14 - Lia Siti Nur'amaliyah; Dewi Seswita Zilda; Nisa Rachmania Mubarik (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2016)
Streptomyces sp. TTA 02 SDS 14 is a transglutaminase producing bacteria which previously had been screened along with more than one hundred isolates. This research aimed to purify and characterize transglutaminase from this strain. Transglutaminase was purified from crude enzyme by ultrafiltration, Q-Sepharose ion exchange chromatography and Sepacryl S200 size exclusion chromatography sequentially, obtaining yield and purification fold of 1.36% and 27 folds, respectively. The molecular weight of the purified transglutaminase was 72 kDa detected by zymogram gel electrophoresis. The optimum temperature and pH were 50°C and 6. The transglutaminase was stable at 45°C and could be activated in the presence of 5 mM and 10 mM of Na+, K+, Li+,Ca2+, Mg2+, BPB (4-bromo-phenacyl bromide), and IAA (iodo acetamide acid), but the activity was inhibited by the presence of Cu+, Zn2+, and PMSF (phenyl methyl sulfonyl fluoride).